Combined Electron Microscopy Approaches for Arterial Glycocalyx Visualization - Chevalier, Laurence; Selim, Jean; Castro, Celia; Cuvilly, Fabien; Baste, Jean-Marc; Richard, Vincent; Pareige, Philippe; Bellien, Jeremy (Frontiers in Cardiovascular Medicine, 2022)
Mainly constituted of glycosaminoglycans and proteoglycans, the glycocalyx is anchored in the plasma membrane, covering, in particular, the extracellular face of the arterial endothelium. Due to its complex 3D architecture, the glycocalyx interacts with a wide variety of proteins, contributing to the vascular permeability, the flow of mechano-transduction, and the modulation of local inflammatory processes. Alterations of glycocalyx structure mediate the endothelial dysfunction and contribute to the aggravation of peripheral vascular diseases. Therefore, the exploration of its ultrastructure becomes a priority to evaluate the degree of injury under physiopathological conditions and to assess the impact of therapeutic approaches. The objective of this study was to develop innovative approaches in electron microscopy to visualize the glycocalyx at the subcellular scale. Intravenous perfusion on rats with a fixing solution containing aldehyde fixatives enriched with lanthanum ions was performed to prepare arterial samples. The addition of lanthanum nitrate in the fixing solution allowed the enhancement of the staining of the glycocalyx for transmission electron microscopy (TEM) and to detect elastic and inelastic scattered electrons, providing complementary qualitative information. The strength of scanning electron microscopy (SEM) was used on resin-embedded serial sections, allowing rapid and efficient large field imaging and previous correlative TEM observations for ultrastructural fine details. To demonstrate the dynamic feature of the glycocalyx, 3D tomography was provided by dual-beam Focus-Ion-Beam-SEM (FIB-SEM). These approaches allowed us to visualize and characterize the ultrastructure of the pulmonary artery glycocalyx under physiological conditions and in a rat pulmonary ischemia-reperfusion model, known to induce endothelial dysfunction. This study demonstrates the feasibility of combined SEM, TEM, and FIB-SEM tomography approaches on the same sample as the multiscale visualization and the identification of structural indicators of arterial endothelial glycocalyx integrity.